2021
DOI: 10.1159/000515912
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Rereview of Normal Cervical Cytologies before High-Grade Cervical Lesions or before Invasive Cervical Cancer

Abstract: Sweden has experienced an unexpected >30% increase in cervical cancer incidence among women with normal cytological screening results. We therefore performed a nationwide assessment of false-negative cytology before invasive cervical cancer. The Swedish national cervical screening registry identified 2,150 normal cytologies taken up to 10 years before 903 cases of invasive cervical cancer. The 27 cytological laboratories in Sweden were asked to rereview the slides, and all of them completed the rerevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 4 publications
2
12
0
Order By: Relevance
“…A recent study in Sweden found an increase in normal cytological screening results prior to diagnosis of invasive cervical cancer, suggesting decreased protection from a benign cytology result due to inadequate cytological diagnosis 6 . This may to some extent be solved with HPV screening, which has proven to have a higher sensitivity compared with cytology 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study in Sweden found an increase in normal cytological screening results prior to diagnosis of invasive cervical cancer, suggesting decreased protection from a benign cytology result due to inadequate cytological diagnosis 6 . This may to some extent be solved with HPV screening, which has proven to have a higher sensitivity compared with cytology 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The cervical cancer screening program was introduced in Sweden in 1967 6 . It has contributed to a substantial decline in cervical cancer incidence and mortality 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, rereviews of normal cytology taken before cervical cancer found that about 30% of slides were discrepant (did not have the same diagnosis on rereview). 23 In summary, we report a large laboratory audit of the testing within the cervical screening program. The fact that we found a consistently high sensitivity should not be taken as evidence that quality control is not needed.…”
Section: Sensitivity Of Cervical Screening During Audit Periodmentioning
confidence: 99%
“…8 A nationwide re-review of normal cytology tests before invasive cervical cancer found a significant increase of false-negative cytology over time, with the proportion increasing on average by 4% per sampling year during 2001 to 2016, suggesting a continuously decreasing protection of cytology over a decade. 9 This problem affects cervical cancer prevention not only in the historical period when cytology was the primary test, but also threatens HPV-based screening as cytology in many settings remains the triage test after HPV-positive findings.…”
Section: Introductionmentioning
confidence: 99%